Risk Attitude, Insurance Patronage and SMEs Performance: Empirical Evidence from Lagos, Nigeria - Sunday Stephen AJEMUNIGBOHUN; Ogorchukwu Augustine ISIMOYA; Ayobami Folarin ELEGUNDE (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2020)
This paper has been to able to ascertain the significant influence of risk attitude on SMEs market share vis-à-vis a relationship between insurance patronage and their financial earnings in the metropolis of Lagos. Descriptive survey design was adopted cum single-stage cluster sampling technique. 256 sample representation produced robust responses through structured questionnaire. Data analytical approach used in this field work were Kolmogorov-Smirnov test method. The research work unravels the significant influence of SMEs’ risk attitude on their market share but at low level. It thus showcased the significant but low relationship between insurance patronage and financial earnings of SMEs in Lagos metropolis. The study recommends therefore that the development of formidable risk management strategies that will help contain subsisting recessionary economic downturn in Nigeria. More so, Stakeholders such as government, insurance practitioners, academics and business tycoons should collaborate and integrate their knowledge, regulatory and financial based resources to help incorporate, implement and fund insurance education curriculum that will facilitate progress, steady growth and development of the youths.